2015
DOI: 10.1002/mop.29087
|View full text |Cite
|
Sign up to set email alerts
|

A Q-band high-gain substrate-integrated waveguide slot antenna

Abstract: agreement between simulation and measurement is achieved while the reflection coefficient of the antennas is less than 28 dB in the 55-65-GHz band. Figures 12 and 13 show the radiation pattern of the fabricated antennas in the E-plane and H-plane. The rows of the metalized via holes placed around the edge of the substrate eliminate the existence of a half-mode SIW that could be a source of undesirable parasitic radiation. In this way, the Eplane radiation pattern of the proposed antennas has a lower ripple. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This approach produces tiny cavities with good microwave performance while preserving the original SIW cavity's field distribution [4][5][6]. In [7][8][9][10][11][12][13][14][15][16], high gain, low-profile SIW antennas for dual-band application are presented by introducing different geometries and cavities in the structure. In literature, the proposed geometries are complex in design.…”
Section: Introductionmentioning
confidence: 99%
“…This approach produces tiny cavities with good microwave performance while preserving the original SIW cavity's field distribution [4][5][6]. In [7][8][9][10][11][12][13][14][15][16], high gain, low-profile SIW antennas for dual-band application are presented by introducing different geometries and cavities in the structure. In literature, the proposed geometries are complex in design.…”
Section: Introductionmentioning
confidence: 99%
“…Single band and dual band mm‐wave antennas for 5G applications were studied in References 1 and 10‐19 . In some of them via‐free microstrip‐fed patch antennas were used, while in others SIW antennas were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…In Reference 17 a pair of triangular slots are used with the SIW antenna to reach a dual-band radiation characteristic. Different shaped slots, like rectangular 18,19 and circular, 20 are implemented with SIW cavity backed structures to reach the desired resonance frequencies. Although good results are obtained in these studies, an expensive Rogers material is used with the reported antennas.…”
Section: Introductionmentioning
confidence: 99%